2021
DOI: 10.3390/ijms222111868
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Idea of Molecular Brains

Abstract: How can single cells without nervous systems perform complex behaviours such as habituation, associative learning and decision making, which are considered the hallmark of animals with a brain? Are there molecular systems that underlie cognitive properties equivalent to those of the brain? This review follows the development of the idea of molecular brains from Darwin’s “root brain hypothesis”, through bacterial chemotaxis, to the recent discovery of neuron-like r-protein networks in the ribosome. By combining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 538 publications
(636 reference statements)
0
25
0
3
Order By: Relevance
“…In general, larger selves (1) are capable of working toward states of affairs that occur farther into the future (perhaps outlasting the lifetime of the agent itself—an important great transition, in the sense of West et al (2015) , along the cognitive continuum); (2) deploy memories further back in time (their actions become less “mechanism” and more decision-making ( Balazsi et al, 2011 ) because they are linked to a network of functional causes and information with larger diameter); and (3) they expend effort to manage sensing/effector activity in larger spaces [from subcellular networks to the extended mind ( Clark and Chalmers, 1998 ; Turner, 2000 ; Timsit and Gregoire, 2021 )]. Overall, increases of agency are driven by mechanisms that scale up stress ( Box 1 )—the scope of states that an agent can possibly be stressed about (in the sense of pressure to take corrective action).…”
Section: Technological Approach To Mind Everywhere: a Proposal For A ...mentioning
confidence: 99%
“…In general, larger selves (1) are capable of working toward states of affairs that occur farther into the future (perhaps outlasting the lifetime of the agent itself—an important great transition, in the sense of West et al (2015) , along the cognitive continuum); (2) deploy memories further back in time (their actions become less “mechanism” and more decision-making ( Balazsi et al, 2011 ) because they are linked to a network of functional causes and information with larger diameter); and (3) they expend effort to manage sensing/effector activity in larger spaces [from subcellular networks to the extended mind ( Clark and Chalmers, 1998 ; Turner, 2000 ; Timsit and Gregoire, 2021 )]. Overall, increases of agency are driven by mechanisms that scale up stress ( Box 1 )—the scope of states that an agent can possibly be stressed about (in the sense of pressure to take corrective action).…”
Section: Technological Approach To Mind Everywhere: a Proposal For A ...mentioning
confidence: 99%
“…Recent studies have shown that microtubules can generate action potential-like electrical oscillations, connecting these proteins to the higher brain functions such as memory and consciousness ( Ballatore et al., 2012 ). Indeed, the recent concepts, “cellular consciousness” and “molecular brains” suggest that cognition and information processing may occur at the cellular level ( Baluška et al., 2021 ; Timsit and Grégoire, 2021 ). Along these lines, neuronal ribosomal proteins and tubulin were showed to form CNS-like circuits with computation power, indicating the possibility of subcellular information processing ( Poirot and Timsit, 2016 ; Chudinova et al., 2019 ; Timsit and Bennequin, 2019 ; Fusco et al., 2021 ).…”
Section: Cell-cell Fusion and Information Processingmentioning
confidence: 99%
“…DNA has and recognizes specific spectral signatures in order to create local and distant connections [ 77 ]. The specific response to DNA oscillations is then handled by the cell's microtubules and microfilaments, just like a chip or a micro-brain [ 77 - 79 ]. This view of biological behavior is based on quantum biology, where we move from the microscale to the nanoscale [ 79 ].…”
Section: Reviewmentioning
confidence: 99%